AIM2 inflammasome mediates Arsenic-induced secretion of IL-1 β and IL-18. (2nd June 2016) - Zhang, Mingfang; Qi, Yuanlin; Li, Hui; Cui, Jiajun; Dai, Lu; Frank, Jacqueline A.; Chen, Jian; Xu, Wenhua; Chen, Gang
ABSTRACT: Chronic sterile inflammation has been implicated in the pathogenesis of many cancers, including skin cancer. Chronic arsenic exposure is closely associated with the development of skin cancer. However, there is a lack of understanding how arsenic induces chronic inflammation in the skin. Interleukin-1 family cytokines play a central role in regulating immune and inflammatory response. IL-1α, IL-1β and IL-18 are three pro-inflammatory cytokines in IL-1 family. Their secretion, especially the secretion of IL-1β and IL-18, is regulated by inflammasomes which are multi-protein complexes containing sensor proteins, adaptor protein and caspase-1. The data from current study show sub-chronic arsenic exposure activates AIM2 inflammasome which in turn activates caspase-1 and enhances the secretion of IL-1β and IL-18 in HaCaT cells and the skin of BALB/c mice. In addition, arsenic-promoted activation of AIM2 inflammasome and increase of IL-1β/IL-18 production are inhibited by PKR inhibitor in HaCaT cells or in the skin of PKR mutant mice, indicating a potential role of PKR in arsenic-induced sterile inflammation.